A stone carving glaze replacing dry granule effect and preparation method thereof

By using stone carving glaze that replaces the dry-grain effect in ceramic products, the problem of easy falling off and cracking during the firing process of dry-grain decoration is solved, and the wear resistance, pollution resistance and acid-base resistance of the ceramic surface is achieved, and product performance and production efficiency are improved.

CN119118513BActive Publication Date: 2025-04-22FOSHAN TAOYING NEW MATERIAL CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411259183.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-10
Publication Date
2025-04-22
Estimated Expiration
2044-09-10

AI Technical Summary

Technical Problem

When existing ceramic products are decorated with dry particles, the protective glaze lacks viscosity to the dry particles, which leads to the dry particles being easily shedded. Too much moisture during the firing process may lead to cracking of the bricks, causing problems of high waste rate and poor performance.

Method used

A stone carving glaze that replaces the dry-grain effect, including base glaze, extruded ink and stone carving glaze, is used to glaze the green surface through the glaze spraying process and is fired in a high-temperature kiln to form an glaze layer with excellent wear resistance, stain resistance and acid and alkali resistance.

Benefits of technology

The deep concave and convex texture on the ceramic surface is realized, which improves wear resistance and corrosion resistance, reduces waste rate and cost, and simplifies the production process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119118513B_ABST
    Figure CN119118513B_ABST
Patent Text Reader

Abstract

The present invention relates to a stone carving glaze that can replace the dry granule effect and a preparation method thereof, and belongs to the technical field of ceramic glaze. The glaze comprises a base glaze, extruded ink and a stone carving glaze material, wherein a base glaze layer is generated by spraying a base glaze slurry on the surface of a green body, and then a pattern layer is formed by spraying the extruded ink on the surface of the base glaze layer, and then the stone carving glaze slurry prepared by ball milling the stone carving glaze material is sprayed on the surface of the pattern layer, and a stone carving glaze with excellent wear resistance and corrosion resistance is obtained by high-temperature calcination. Through the process of the present invention, a ceramic surface with a deep concave-convex texture can be prepared, and the anti-fouling and corrosion resistance are strong, which is simpler than the dry granule process and greatly reduces the cost.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of ceramic glazes and relates to a stone carving glaze replacing dry particle effects and a preparation method thereof. Background Art

[0002] Competition in building ceramic products is increasingly fierce, and consumers have higher and higher requirements for ceramic surface performance, especially in terms of ceramic surface hardness, surface decoration methods, surface anti-slip and surface functionalization. One of the important competition directions is the competition of patterns and varieties, and the focus of competition is the level of product design and decorative materials. Ceramic products using dry particles as decoration have come into being. At present, for decorative ceramic products using dry particles, the main method is to directly spread dry particles and apply protective glaze. Since the protective glaze has no stickiness to the dry particles, it cannot fix the dry particles, causing the dry particles to fall off easily. They need to be dried separately before firing. Otherwise, if there is too much water in the brick blank when entering the kiln, it will cause the brick body to crack after entering the kiln for firing. The scrap rate of the ceramic bricks produced is high, the performance is poor, and the cost of using dry particles is too high.

[0003] The invention discloses a stone carving glaze which can replace the dry particle effect and a preparation method thereof, which can greatly reduce the cost of raw materials, and can meet the dry particle characteristics no matter which glazing process is used, has a simple production process, clear lines, a strong three-dimensional sense, a wider firing range, and the finished product after firing is more wear-resistant and corrosion-resistant, thereby improving the yield rate. Summary of the invention

[0004] The purpose of the present invention is to provide a stone carving glaze which can replace the dry particle effect and a preparation method thereof. The prepared stone carving glaze has excellent wear resistance and antifouling properties and strong tolerance to acid and alkali.

[0005] The purpose of the present invention can be achieved through the following technical solutions:

[0006] A stone carving glaze that replaces the dry granule effect, comprising a base glaze, extrusion ink and a stone carving glaze, wherein the base glaze comprises the following components calculated by weight percentage: 5-10% nepheline, 20-28% albite, 4-8% kaolin, 2-4% ball clay, 4-8% calcined alumina, 12-18% quartz, 4-8% barium carbonate, 12-20% potassium feldspar, 3% zinc oxide and 10-17% low-temperature frit;

[0007] The chemical composition of the squeezing ink is: 5.56% Al2O3, 63.67% SiO2, 16.71% CaO, 1.42% MgO, 2.64% K2O, 7.35% ZnO, and 2.65% loss on ignition LOSS;

[0008] The stone carving glaze comprises the following components: 40-50% high temperature frit, 5-10% modified kaolin, 35-45% quartz, and 5-10% burnt clay;

[0009] The preparation process of modified kaolin is as follows:

[0010] S11, by weight, treating kaolin with an alkaline solution for 30 to 50 minutes, and after drying, heating the kaolin to 130 to 140°C at a rate of 1 to 3°C / min, keeping the temperature for 20 minutes, and then heating the kaolin to 230 to 250°C at a rate of 2 to 5°C / min, keeping the temperature for 1.5 to 2.5 hours, and then air-cooling to room temperature;

[0011] S12, at 80-95°C, stir and keep 8-12 parts of kaolin cooled to room temperature, 3-5 parts of ferric oxalate and 65-80 parts of water for 7-9 hours, and continue to heat to 100-110°C and dry for 8-11 hours;

[0012] S13, adding 4 to 7 parts of modified zinc oxide, 1 to 3 parts of surfactant and 2 to 4 parts of coupling agent, mixing evenly, ball milling and drying to obtain modified kaolin.

[0013] As a preferred technical solution of the present invention, the chemical composition of the low-temperature frit is: Al2O3: 8.58%, SiO2: 46.58%, CaO: 16.61%, MgO: 4.45%, BaO: 12.74%, NaO: 4.21%, K2O: 2.51%, B2O3: 4.32%.

[0014] As a preferred technical solution of the present invention, the chemical composition of the high-temperature melt is: Al2O3: 22.58%, SiO2: 46.58%, CaO: 17.01%, MgO: 0.95%, BaO: 1.35%, Na2O: 0.96%, K2O: 3.39%, B2O3: 0.42%, ZnO: 6.76%.

[0015] As a preferred technical solution of the present invention, in step S11, the alkaline solution is a sodium hydroxide or potassium hydroxide aqueous solution with a mass fraction of 20-25%.

[0016] As a preferred technical solution of the present invention, in step S11, the solid-to-liquid ratio of kaolin to alkaline solution is 1:20 g / mL.

[0017] As a preferred technical solution of the present invention, in step S13, the preparation process of the modified zinc oxide is as follows:

[0018] In parts by weight, 5 to 8 parts of zinc sulfate are added to 100 to 150 parts of water and stirred to dissolve, and then 10 to 12 parts of potassium hydroxide and 2 to 4 parts of tantalum oxide are added. After stirring at a speed of 500 r / min for 3 hours, the mixture is kept warm at 130 to 150° C. for 9 to 11 hours. After filtering, the solid is calcined at 450 to 510° C. for 3 to 4.5 hours to prepare the modified zinc oxide.

[0019] As a preferred technical solution of the present invention, in step S13, the coupling agent is one of KH560 and KH570.

[0020] As a preferred technical solution of the present invention, in step S13, the surfactant is one of stearic acid, sodium dodecyl sulfate and sodium dodecyl sulfonate.

[0021] A method for preparing a stone carving glaze that replaces the dry particle effect comprises the following steps:

[0022] S91, base glaze slurry preparation:

[0023] According to the formula ratio, the components of the base glaze are mixed evenly and placed in a ball mill. After grinding at a speed of 400 r / min for 1 to 2 hours, 40 wt% of water, 0.15 wt% of sodium carboxymethyl cellulose and 0.35 wt% of sodium tripolyphosphate are added, and the speed is maintained to continue grinding for 8 hours. The base glaze slurry is prepared by sieving and removing iron with a magnetic iron remover.

[0024] S92, bottom glaze:

[0025] The base glaze slurry is applied on the surface of the green body by spraying glaze. The specific gravity of the glaze water is 1.55-1.60g / ml and the spraying amount is 90-120g / m 2 , forming a bottom glaze layer;

[0026] S93, inkjet:

[0027] The squeezing ink is sprayed on the surface of the base glaze layer by intelligent inkjet printing to form a pattern layer;

[0028] S94, Stone carving glaze slurry glazing:

[0029] According to the formula ratio, the components of the stone carving glaze are mixed evenly and placed in a ball mill. After grinding at a speed of 400r / min for 1-2h, 40wt% of water, 0.15wt% of sodium carboxymethyl cellulose and 0.35wt% of sodium tripolyphosphate are added to the stone carving glaze. The speed is maintained and the grinding is continued for 8h. The magnetic iron remover is used to remove iron to prepare the stone carving glaze slurry. The stone carving glaze slurry is applied to the pattern layer through the glaze spraying process. When spraying the glaze, the glaze water specific gravity is 1.35-1.40g / ml and the glaze spraying amount is 80-100g / m 2 ;

[0030] S95, Sintering:

[0031] After the stone carving glaze slurry is sprayed, it is fired in a kiln at 1160° C. for 35 minutes to prepare the stone carving glaze having the effect of replacing dry particles.

[0032] The high-temperature frit in the formula of the present invention mainly increases the melting performance of the glaze, making the glaze layer denser and more sintered, increasing the initial melting temperature of the formula, making the glaze layer more three-dimensional, the kaolin improves the suspension of the glaze slurry, and the quartz makes the glaze layer more three-dimensional, with stronger permeability and a thicker glaze layer after melting; the burnt clay mainly increases the refractoriness of the aluminum oxide in the formula, and the zinc oxide mainly increases the firing range of the formula and increases the color level; at the same time, adding the low-temperature frit can reduce the viscosity of the glaze, thereby making the melt more fluid, and at the same time, a glass phase can be formed in the glaze, so that the glaze has a certain elasticity, can absorb and relieve the thermal expansion and contraction stress of the ceramic, and reduce the occurrence of thermal cracks.

[0033] When preparing the modified kaolin, the present invention firstly performs alkali treatment to make the components (such as SiO2) in the kaolin react with the alkali, enrich the pore structure of the kaolin, increase the small pore structure, improve the porosity, and remove the impurity oxides (iron, manganese, copper) in the kaolin, thereby improving the purity of the kaolin; and the alkali treatment can change the particle state of the kaolin to make it more uniform and fine; and then roasting at a temperature of about 200 degrees to remove part of the adsorbed water, bound water and low-boiling organic impurities still existing in the kaolin, which helps to reduce the glaze after being used. Bubbles are formed during the firing process, which improves the smoothness of the glaze surface and helps the glaze layer to form a denser and harder structure during the firing process, thereby helping to improve the hardness of the ceramic product; kaolin is immersed in a ferric oxalate solution. On the one hand, ferric oxalate can dissolve the iron oxides on the surface of the kaolin and improve the whiteness of the kaolin; at the same time, the iron ions in the ferric oxalate can exchange with the cations between the kaolin layers, changing the interlayer charge distribution and interlayer spacing of the kaolin; thus, after the modified zinc oxide is mixed with kaolin, the modified zinc oxide can be more easily intercalated into the kaolin layer.

[0034] Modified zinc oxide uniformly mixed with tantalum oxide is obtained by mixed roasting of soluble zinc salt and tantalum oxide. Tantalum oxide has high strength and hardness, and can improve the hardness of zinc oxide. Inserting it into the interlayer of kaolin can significantly improve the mechanical strength of kaolin used in ceramic glazes. At the same time, tantalum oxide and zinc oxide can jointly affect the crystallization behavior of the glaze during sintering, promote liquid phase separation during sintering, and help the glaze to have a more stable physical state during sintering through the high stability of modified zinc oxide, thereby forming a more stable and dense glaze layer structure. When preparing modified kaolin, adding a coupling agent can not only form chemical bonds with modified zinc oxide ions during ball milling, but also form hydrogen bonds with hydroxyl groups on the surface of kaolin, which can increase the cross-linking density inside the kaolin, thereby improving the strength, and further enhance the intercalation bonding between the modified zinc oxide particles and kaolin, thereby improving the hardness and corrosion resistance of the modified kaolin.

[0035] Beneficial effects of the present invention:

[0036] The invention prepares a stone carving glaze capable of replacing dry granule effects, comprising a base glaze, extruded ink and a stone carving glaze material. A base glaze layer is generated by spraying a base glaze slurry on the surface of a green body, a pattern layer is formed by spraying the extruded ink on the surface of the base glaze layer, and then the stone carving glaze material is ball-milled to obtain a stone carving glaze slurry to be sprayed on the surface of the pattern layer. The stone carving glaze with excellent wear resistance and corrosion resistance is obtained by high-temperature sintering, thereby avoiding the problem of low performance of ceramic tiles caused by using dry granules in traditional processes.

[0037] Through the process of the present invention, a ceramic surface with deep concave-convex texture can be prepared, which has strong anti-fouling and corrosion resistance, is simpler than the dry granulation process, and greatly reduces the formulation and labor costs. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] In order to facilitate understanding by those skilled in the art, the present invention is further described below with reference to the accompanying drawings.

[0039] Figure 1 This is a glaze effect diagram of the stone carving glaze prepared in Example 1 to replace the dry particle effect. DETAILED DESCRIPTION

[0040] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in combination with the embodiments.

[0041] In the following examples and comparative examples:

[0042] The chemical composition of the low-temperature frit is: Al2O3: 8.58%, SiO2: 46.58%, CaO: 16.61%, MgO: 4.45%, BaO: 12.74%, NaO: 4.21%, K2O: 2.51%, B2O3: 4.32%.

[0043] The chemical composition of the high-temperature frit is: Al2O3: 22.58%, SiO2: 46.58%, CaO: 17.01%, MgO: 0.95%, BaO: 1.35%, Na2O: 0.96%, K2O: 3.39%, B2O3: 0.42%, ZnO: 6.76%.

[0044] The chemical composition of the squeezing ink is: 5.56% Al2O3, 63.67% SiO2, 16.71% CaO, 1.42% MgO, 2.64% K2O, 7.35% ZnO, 2.65% loss on ignition LOSS;

[0045] Example 1

[0046] The base glaze comprises, by weight percentage, 5% nepheline, 28% albite, 4% kaolin, 4% ball clay, 4% calcined alumina, 18% quartz, 4% barium carbonate, 20% potassium feldspar, 3% zinc oxide and 10% low-temperature frit;

[0047] The stone carving glaze includes: 40% high temperature frit, 10% modified kaolin, 45% quartz, 5% burnt clay;

[0048] Preparation of modified kaolin:

[0049] S11, by weight, treating kaolin with a 20% sodium hydroxide aqueous solution for 30 minutes, the solid-liquid ratio of kaolin to the alkaline solution being 1:20 g / mL, and after drying, heating the kaolin to 130°C at a rate of 1°C / min, keeping the temperature for 20 minutes, and then heating the temperature to 230°C at a rate of 2°C / min, keeping the temperature for 1.5 hours, and then air-cooling to room temperature;

[0050] S12, 8 parts of kaolin cooled to room temperature, 3 parts of ferric oxalate and 65 parts of water were stirred and kept warm for 7 hours at 80°C, and then the temperature was raised to 100°C and dried for 8 hours;

[0051] S13, add 4 parts of modified zinc oxide, 1 part of stearic acid and 2 parts of KH560, mix evenly, and obtain modified kaolin by ball milling and drying.

[0052] Preparation of modified zinc oxide:

[0053] In parts by weight, 5 parts of zinc sulfate are added to 100 parts of water and stirred to dissolve, and then 10 parts of potassium hydroxide and 2 parts of tantalum oxide are added. After stirring at a speed of 500 r / min for 3 hours, the mixture is kept warm at 130° C. for 9 hours. After filtering, the solid is calcined at 450° C. for 3 hours to prepare the modified zinc oxide.

[0054] Preparation of stone glaze to replace dry granule effect:

[0055] S91, base glaze slurry preparation:

[0056] According to the formula ratio, the components of the base glaze are evenly mixed and placed in a ball mill. After grinding at a speed of 400r / min for 1h, 40wt% of water, 0.15wt% of sodium carboxymethyl cellulose and 0.35wt% of sodium tripolyphosphate are added, and the speed is maintained to continue grinding for 8h. The base glaze slurry is prepared by sieving and removing iron with a magnetic iron remover;

[0057] S92, bottom glaze:

[0058] The base glaze slurry is applied on the surface of the green body by spraying glaze. The specific gravity of the glaze water is 1.55g / ml and the spraying amount is 90g / m 2 , forming a bottom glaze layer;

[0059] S93, inkjet:

[0060] The squeezing ink is sprayed on the surface of the base glaze layer by intelligent inkjet printing to form a pattern layer;

[0061] S94, Stone carving glaze slurry glazing:

[0062] According to the formula ratio, the components of the stone carving glaze are mixed evenly and placed in a ball mill. After grinding at a speed of 400r / min for 1h, 40wt% of water, 0.15wt% of sodium carboxymethyl cellulose and 0.35wt% of sodium tripolyphosphate are added to the stone carving glaze. The speed is maintained and grinding is continued for 8h. The magnetic iron remover is used to remove iron to prepare the stone carving glaze slurry. The stone carving glaze slurry is applied to the pattern layer through the glaze spraying process. The glaze water specific gravity during glaze spraying is 1.35g / ml and the glaze spraying amount is 80g / m 2 ;

[0063] S95, Sintering:

[0064] After the stone carving glaze slurry is sprayed, it is fired in a kiln at 1160° C. for 35 minutes to prepare the stone carving glaze having the effect of replacing dry particles.

[0065] Example 2

[0066] The base glaze comprises, by weight percentage, 8% nepheline, 25% albite, 6% kaolin, 3% ball clay, 6% calcined alumina, 15% quartz, 6% barium carbonate, 14% potassium feldspar, 3% zinc oxide and 14% low-temperature frit;

[0067] The stone carving glaze includes: 45% high temperature frit, 8% modified kaolin, 40% quartz, 7% burnt clay;

[0068] Preparation of modified kaolin:

[0069] S11. In parts by weight, kaolin was treated with a 22% sodium hydroxide aqueous solution for 40 minutes, and the solid-liquid ratio of kaolin to the alkaline solution was 1:20 g / mL. After drying, the kaolin was heated to 135°C at a rate of 2°C / min, and kept warm for 20 minutes, and then heated to 240°C at a rate of 3°C / min, and kept warm for 2 hours, and then air-cooled to room temperature;

[0070] S12. At 85°C, 10 parts of kaolin cooled to room temperature, 4 parts of ferric oxalate and 72 parts of water were stirred and kept warm for 8 hours, and then the temperature was raised to 105°C and dried for 10 hours;

[0071] S13, add 5 parts of modified zinc oxide, 2 parts of stearic acid and 3 parts of KH570, mix evenly, and obtain modified kaolin by ball milling and drying.

[0072] Preparation of modified zinc oxide:

[0073] In parts by weight, 7 parts of zinc sulfate are added to 120 parts of water and stirred to dissolve, and then 11 parts of potassium hydroxide and 3 parts of tantalum oxide are added. After stirring at a speed of 500 r / min for 3 hours, the mixture is kept at 140° C. for 10 hours. After filtering, the solid is calcined at 480° C. for 4 hours to prepare the modified zinc oxide.

[0074] Preparation of stone glaze to replace dry granule effect:

[0075] S91, base glaze slurry preparation:

[0076] According to the formula ratio, the components of the base glaze are evenly mixed and placed in a ball mill. After grinding at a speed of 400r / min for 1.5h, 40wt% of water, 0.15wt% of sodium carboxymethyl cellulose and 0.35wt% of sodium tripolyphosphate are added, and the speed is maintained to continue grinding for 8h. The base glaze slurry is prepared by sieving and removing iron with a magnetic iron remover;

[0077] S92, bottom glaze:

[0078] The base glaze slurry is applied on the surface of the green body by spraying glaze. The specific gravity of the glaze water is 1.57g / ml and the spraying amount is 110g / m 2, forming a bottom glaze layer;

[0079] S93, inkjet:

[0080] The squeezing ink is sprayed on the surface of the base glaze layer by intelligent inkjet printing to form a pattern layer;

[0081] S94, Stone carving glaze slurry glazing:

[0082] According to the formula ratio, the components of the stone carving glaze are mixed evenly and placed in a ball mill. After grinding at a speed of 400r / min for 1.5h, 40wt% of water, 0.15wt% of sodium carboxymethyl cellulose and 0.35wt% of sodium tripolyphosphate are added to the stone carving glaze. The speed is maintained and grinding is continued for 8h. A magnetic iron remover is used to remove iron to prepare a stone carving glaze slurry. The stone carving glaze slurry is applied to the pattern layer through a glaze spraying process. The glaze water specific gravity during glaze spraying is 1.38g / ml and the glaze spraying amount is 90g / m 2 ;

[0083] S95, Sintering:

[0084] After the stone carving glaze slurry is sprayed, it is fired in a kiln at 1160° C. for 35 minutes to prepare the stone carving glaze having the effect of replacing dry particles.

[0085] Example 3

[0086] The base glaze comprises, by weight percentage, 10% nepheline, 20% albite, 8% kaolin, 2% ball clay, 8% calcined alumina, 12% quartz, 8% barium carbonate, 12% potassium feldspar, 3% zinc oxide and 17% low-temperature frit;

[0087] The stone carving glaze includes: 50% high temperature frit, 5% modified kaolin, 35% quartz, 10% burnt clay;

[0088] Preparation of modified kaolin:

[0089] S11. In parts by weight, kaolin was treated with a 25% sodium hydroxide aqueous solution for 50 minutes, and the solid-liquid ratio of kaolin to the alkaline solution was 1:20 g / mL. After drying, the kaolin was heated to 140°C at a rate of 3°C / min, and kept warm for 20 minutes, and then heated to 250°C at a rate of 5°C / min, and kept warm for 2.5 hours, and then air-cooled to room temperature;

[0090] S12. At 95°C, 12 parts of kaolin cooled to room temperature, 5 parts of ferric oxalate and 80 parts of water were stirred and kept warm for 9 hours, and then the temperature was raised to 110°C and dried for 11 hours;

[0091] S13, add 7 parts of modified zinc oxide, 3 parts of sodium dodecyl sulfate and 4 parts of KH560, mix evenly, and obtain modified kaolin by ball milling and drying.

[0092] Preparation of modified zinc oxide:

[0093] In parts by weight, 8 parts of zinc sulfate are added to 150 parts of water and stirred to dissolve, and then 12 parts of potassium hydroxide and 4 parts of tantalum oxide are added. After stirring at a speed of 500 r / min for 3 hours, the mixture is kept at 150° C. for 11 hours. After filtering, the solid is calcined at 510° C. for 4.5 hours to prepare the modified zinc oxide.

[0094] Preparation of stone glaze to replace dry granule effect:

[0095] S91, base glaze slurry preparation:

[0096] According to the formula ratio, the components of the base glaze are evenly mixed and placed in a ball mill. After grinding at a speed of 400r / min for 2h, 40wt% of water, 0.15wt% of sodium carboxymethyl cellulose and 0.35wt% of sodium tripolyphosphate are added, and the speed is maintained to continue grinding for 8h. The base glaze slurry is prepared by sieving and removing iron with a magnetic iron remover;

[0097] S92, bottom glaze:

[0098] The base glaze slurry is applied on the surface of the green body by spraying glaze. The specific gravity of the glaze water is 1.60g / ml and the spraying amount is 120g / m 2 , forming a bottom glaze layer;

[0099] S93, inkjet:

[0100] The squeezing ink is sprayed on the surface of the base glaze layer by intelligent inkjet printing to form a pattern layer;

[0101] S94, Stone carving glaze slurry glazing:

[0102] According to the formula ratio, the components of the stone carving glaze are mixed evenly and placed in a ball mill. After grinding at a speed of 400r / min for 2h, 40wt% of water, 0.15wt% of sodium carboxymethyl cellulose and 0.35wt% of sodium tripolyphosphate are added to the stone carving glaze. The speed is maintained and grinding is continued for 8h. A magnetic iron remover is used to remove iron to prepare a stone carving glaze slurry. The stone carving glaze slurry is applied to the pattern layer through a glaze spraying process. The glaze water specific gravity during glaze spraying is 1.40g / ml and the glaze spraying amount is 100g / m 2 ;

[0103] S95, Sintering:

[0104] After the stone carving glaze slurry is sprayed, it is fired in a kiln at 1160° C. for 35 minutes to prepare the stone carving glaze having the effect of replacing dry particles.

[0105] Comparative Example 1

[0106] The difference between Comparative Example 1 and Example 1 is that the zinc oxide in Comparative Example 1 is not modified, and the other operations are the same.

[0107] Comparative Example 2

[0108] The difference between Comparative Example 2 and Example 1 is that the kaolin in Comparative Example 2 is not treated with ferric oxalate, and the other operations are the same.

[0109] Comparative Example 3

[0110] The difference between Comparative Example 3 and Example 1 is that in Comparative Example 3, kaolin is not mixed with modified zinc oxide for ball milling, and the other operations are the same.

[0111] Comparative Example 4

[0112] The difference between Comparative Example 4 and Example 1 is that the kaolin in Comparative Example 4 has not been subjected to any modification treatment, and the other operations are the same.

[0113] Performance Testing:

[0114] The stone carving glaze surface with the dry particle replacement effect obtained by the implementation and comparative examples was tested.

[0115] Wear resistance: GB / T3810.7-2016,

[0116] Stain resistance: According to GB / T 3810.14-2016,

[0117] Corrosion resistance: The products prepared in the example and the comparative example were placed in a 5wt% nitric acid solution and a 20wt% potassium hydroxide solution respectively. After being placed for 12 hours, the changes on the surface of the ceramic products were observed. The results are as follows:

[0118]

[0119]

[0120] It can be seen from the above data that the wear resistance of the embodiments of the present invention can reach level 4, while the wear resistance level and stain resistance of the comparative examples are lower than those of the embodiments; at the same time, the surfaces of the ceramic products made from the glazes of comparative examples 1 and comparative examples 3-4 are corroded, while the surfaces of the ceramic products obtained from the embodiments of the present invention do not change, indicating that the present invention has good acid and alkali corrosion resistance.

[0121] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.

Claims

1. A stone carving glaze that replaces the dry particle effect, characterized in that: The invention comprises a base glaze, an extruded ink and a stone carving glaze, wherein the base glaze comprises the following components calculated by weight percentage: 5-10% nepheline, 20-28% albite, 4-8% kaolin, 2-4% ball clay, 4-8% calcined alumina, 12-18% quartz, 4-8% barium carbonate, 12-20% potassium feldspar, 3% zinc oxide and 10-17% low-temperature frit; The chemical composition of the squeezing ink is: 5.56% Al2O3, 63.67% SiO2, 16.71% CaO, 1.42% MgO, 2.64% K2O, 7.35% ZnO, 2.65% loss on ignition; The stone carving glaze comprises the following components: 40-50% high temperature frit, 5-10% modified kaolin, 35-45% quartz, and 5-10% burnt clay; The preparation process of modified kaolin is as follows: S11, by weight, treating kaolin with an alkaline solution for 30-50 minutes, and after drying, heating the kaolin to 130-140°C at a rate of 1-3°C / min, keeping the temperature for 20 minutes, and then heating it to 230-250°C at a rate of 2-5°C / min, keeping the temperature for 1.5-2.5 hours, and then air-cooling it to room temperature; S12, at 80-95°C, stir and keep 8-12 parts of kaolin cooled to room temperature, 3-5 parts of ferric oxalate and 65-80 parts of water for 7-9 hours, and continue to heat to 100-110°C and dry for 8-11 hours; S13, adding 4-7 parts of modified zinc oxide, 1-3 parts of surfactant and 2-4 parts of coupling agent, mixing evenly, ball milling and drying to obtain modified kaolin.

2. The stone carving glaze replacing the dry particle effect according to claim 1, characterized in that: The chemical composition of the low-temperature frit is: Al2O3: 8.58%, SiO2: 46.58%, CaO: 16.61%, MgO: 4.45%, BaO: 12.74%, NaO: 4.21%, K2O: 2.51%, B2O3: 4.32%.

3. The stone carving glaze replacing the dry particle effect according to claim 1, characterized in that: The chemical composition of the high-temperature frit is: Al2O3: 22.58%, SiO2: 46.58%, CaO: 17.01%, MgO: 0.95%, BaO: 1.35%, Na2O: 0.96%, K2O: 3.39%, B2O3: 0.42%, and ZnO: 6.76%.

4. The stone carving glaze replacing the dry particle effect according to claim 1, characterized in that: In step S11, the alkaline solution is a sodium hydroxide or potassium hydroxide aqueous solution with a mass fraction of 20-25%.

5. The stone carving glaze replacing dry particle effect according to claim 1, characterized in that: In step S11, the solid-liquid ratio of kaolin to alkaline solution is 1:20 g / mL.

6. The stone carving glaze replacing dry particle effect according to claim 1, characterized in that: In step S13, the preparation process of the modified zinc oxide is as follows: In parts by weight, 5 to 8 parts of zinc sulfate are added to 100 to 150 parts of water and stirred to dissolve, and then 10 to 12 parts of potassium hydroxide and 2 to 4 parts of tantalum oxide are added. After stirring at a speed of 500 r / min for 3 hours, the mixture is kept warm at 130 to 150° C. for 9 to 11 hours. After filtering, the solid is calcined at 450 to 510° C. for 3 to 4.5 hours to prepare the modified zinc oxide.

7. The stone carving glaze replacing the dry particle effect according to claim 1, characterized in that: In step S13, the coupling agent is one of KH560 and KH570.

8. The stone carving glaze replacing dry particle effect according to claim 1, characterized in that: In step S13, the surfactant is one of stearic acid, sodium dodecyl sulfate and sodium dodecyl sulfonate.

9. A method for preparing a stone carving glaze replacing dry particle effect as claimed in any one of claims 1 to 8, characterized in that: The following steps are involved: S91, base glaze slurry preparation: According to the formula ratio, the components of the base glaze are mixed evenly and placed in a ball mill. After grinding at a speed of 400 r / min for 1-2 hours, 40 wt% of water, 0.15 wt% of sodium carboxymethyl cellulose and 0.35 wt% of sodium tripolyphosphate are added, and the speed is maintained to continue grinding for 8 hours. The base glaze slurry is prepared by sieving and removing iron with a magnetic iron remover. S92, bottom glaze: The base glaze slurry is applied on the surface of the green body by spraying glaze. The specific gravity of the glaze water is 1.55~1.60 g / ml and the spraying amount is 90~120g / m 2 , forming a bottom glaze layer; S93, inkjet: The squeezing ink is sprayed on the surface of the base glaze layer by intelligent inkjet printing to form a pattern layer; S94, Stone carving glaze slurry glazing: According to the formula ratio, the components of the stone carving glaze are mixed evenly and placed in a ball mill. After grinding at a speed of 400r / min for 1-2h, 40wt% of water, 0.15wt% of sodium carboxymethyl cellulose and 0.35wt% of sodium tripolyphosphate are added to the stone carving glaze. The speed is maintained and the grinding is continued for 8h. The magnetic iron remover is used to remove iron to prepare the stone carving glaze slurry. The stone carving glaze slurry is applied to the pattern layer through the glaze spraying process. The glaze water specific gravity during glaze spraying is 1.35-1.40 g / ml and the glaze spraying amount is 80-100g / m 2 ; S95, Sintering: After the stone carving glaze slurry is sprayed, it is fired in a kiln at 1160° C. for 35 minutes to prepare the stone carving glaze having the effect of replacing dry particles.

Citation Information

Patent Citations

  • High-lustre dry-particle polished ceramic large plate, and preparation method thereof

    CN108424111A

  • High-wear-resistance marble-imitated ceramic tile and preparation method thereof

    CN112592063A